Aceh as The Role Model of Democratic Management Success: Critical Discourses Analysis - Chairuddin Chairuddin; M Manugeren; Jumino Suhadi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study analyzes the news narrative “Aceh Tak Masuk Daerah Rawan Pilkada Serentak, Lima Provinsi Memiliki Potensi Tinggi” using Van Dijk’s Critical Discourse Analysis (CDA) model to explore Aceh’s portrayal as a role model of democratic success. The research aims to uncover how this narrative influences perceptions of Aceh’s stability among local and national audiences, particularly in contrast to its historical association with conflict. This study adopts a qualitative approach, employing Van Dijk’s CDA framework, which consists of three dimensions: textual analysis, social cognition, and sociopolitical context. The data were collected through a textual analysis of media discourse and audience surveys involving 47 respondents (37 from Aceh and 10 from outside Aceh). The textual analysis focuses on the structural composition of the news, while the audience survey examines how different groups perceive the narrative. The results indicate that 72.73% of local respondents express pride in Aceh’s depiction as a safe and stable region, yet 43.24% remain neutral about its relevance to current realities. Among national respondents, 100% perceive the narrative positively, with 50% strongly agreeing that Aceh serves as a model for democratic management. These findings demonstrate that media discourse effectively challenges stereotypes and promotes a positive image of Aceh, particularly to national audiences. However, local acceptance requires narratives grounded in authentic experiences. This study contributes to discourse analysis by showing how positive discourse can transform public perception, highlighting its potential to promote post-conflict regions as examples of democratic success.